2021
DOI: 10.1027/1015-5759/a000623
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Concept and Identity Measure in Adolescents

Abstract: Abstract. Identity difficulties have been associated with various psychiatric conditions and are considered a central issue in personality pathology. Following the Alternative Model for Personality Disorders, measures of self- and interpersonal functioning have been developed. Although these measures were intended to be separate ratings of self-other deficits, only a global rating was obtained. Moreover, these measures fall short in bridging the gap between developmental and clinical identity work. To capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 37 publications
(68 reference statements)
6
22
0
Order By: Relevance
“…Here, we demonstrate that the AIDA taps the latent construct of maladaptive identity development similarly across adolescent age groups so that meaningful developmental inferences and comparisons can be made. Other studies have shown similar age invariance of measures of adaptive identity function based on Erikson's ( 13) model [e.g., (63)] as well as maladaptive identity function (64). This should facilitate further work in continuity and change also for within person development studies of maladaptive identity.…”
Section: Discussionsupporting
confidence: 51%
“…Here, we demonstrate that the AIDA taps the latent construct of maladaptive identity development similarly across adolescent age groups so that meaningful developmental inferences and comparisons can be made. Other studies have shown similar age invariance of measures of adaptive identity function based on Erikson's ( 13) model [e.g., (63)] as well as maladaptive identity function (64). This should facilitate further work in continuity and change also for within person development studies of maladaptive identity.…”
Section: Discussionsupporting
confidence: 51%
“…In a previous study in community adults (in Sample 1 of this study), the Dutch version of the SCIM yielded reliable and valid test scores if items 11 and 16 were excluded from the calculation of the total score in the adult samples (Bogaerts et al, 2018). In a validation study in an adolescent sample (Sample 3 of this study), four items (items 3, 11, 16, and 18) needed to be excluded to obtain valid and reliable test scores (Bogaerts et al, 2021b). In the adult samples of the present study (for the 25-item version of the SCIM), Cronbach's alpha coefficients for consolidated identity, disturbed identity, and lack of identity were .64, .81, and .87, respectively (Sample 1) and .75, .82, and .91, respectively (Sample 2).…”
Section: Identity Functioningmentioning
confidence: 83%
“…Our second objective was to investigate convergent validity of the FISSPD with an identity measure, both in adolescents and adults. Based on previous literature (Bogaerts et al, 2018;Bogaerts et al, 2021a;Bogaerts et al, 2021b;Kaufman et al, 2015), the FISSPD was expected to be negatively associated with consolidated identity and positively associated with disturbed identity and lack of identity.…”
Section: Current Studymentioning
confidence: 93%
See 1 more Smart Citation
“…Since we consider this to be a limitation of our research, future studies should include instruments that are validated in the culture of the study as well as other scales to measure convergent and discriminant validity. Also, future studies should include other measurements for discriminant validity, such as Extraversion or Openness (Bogaerts et al, 2021;Keng et al, 2018). One instrument that measures both extraversion and openness is the Big Five Inventory, used in the study of Keng and collaborators (2018).…”
Section: Discussionmentioning
confidence: 99%